ANALISIS KECEPATAN KENDARAAN MOBIL COLT L300 SOLAR SAAT MENANJAK 300 DENGAN BEBAN PENUH TRAYEK PEKAN BARU - PASIR PENGARAIAN - Suminto - (Universitas Pasir Pengaraian, 2009)
The road condition and the Sumetera island climate is influence the endure capabilitythe transportation. The road condition can be see from the slanting, oblique and turns. Thecariability and the road surface. It alot of turn and slanting road, this condition it’s hard to be avoidin make highway, moreover in hill. The slanting is about 0 – 300and turns in certain place can be 10m in rotate. The couse chose the vehicle with 10 man capacity is for pleasant the passanger cousethe distance aout 300 km. The circle of machine (μm) it influence by the size of the machine. Wherethe machine circle connected with the reduction system transmission and continued by the Wheelit’s make the vihicle move. The circle motor can be define by the Wheel size, máximum speed,rolling resistance, air resistance and gradiebt resistance. From the count of the tire size, maximunspeed and wheel size then find the máximum circle motor is 3470 rpm. From the count of rollingresistance, air resistance and gradient resistance can be find power 68,33 Hp and speed at slantingup with full load is 5 km/h.